Athletic trainers' barriers to maintaining professional commitment in the collegiate setting - Mazerolle, S. M.; Eason, C. M.; Pitney, W. A. (Journal of Athletic Training, 2015)
Context: Professional commitment simply describes one's obligation to his or her work. For athletic trainers (ATs), the demanding work environment and job expectations may affect their characterization of professional commitment. Our breadth of knowledge regarding professional commitment within athletic training is narrow.